O uso da calculadora como recurso de tecnologia assistiva no ensino de aritmética para os alunos com deficiência intelectual inseridos na Educação de Jovens e Adultos (EJA) - Rodrigues, Lis Borges (2015)
By acting in the pedagogical coordination and follow up the difficulties presented by some teachers to teach mathematical concepts to adult learners, especially those with intellectual disabilities, the Elementary School entered in the Youth and Adult Education, became interested in investigating: How calculator is sets as an Assistive Technology for numeracy teaching for students with Intellectual Disabilities in Elementary Education of EJA and what are the possible impacts of using these technologies in the learning of these students? From that context began the research that is object is numeracy teaching for students with intellectual disabilities through the use of the calculator as an Assistive Technology feature. This question gave rise to this work, carried out through a qualitative research, the method is a method of educational intervention research, whose main objective is to develop a proposal for a pedagogical intervention with the use of Assistive Technology. It was used as a theoretical contribution of authors who address and discuss topics: Mathematics Education, Youth and Adult Education, Inclusive Education and Intellectual Disability whose understandings and theoretical concepts run counter to established to carry out this work. Some authors have referred to us were Freire (1987), D'Ambrósio (1990); Fonseca (2012); Ponte (1989; 1992; 2014); Vygotsky (1994, 2001, 2004, 2014); Moysés (2012); Machado (2013); Mantoan (2003, 2006a; 2006b); Vargas; Maia (2011); Paulon; Freitas; Pinho (2005) and Vasconcellos (1995). Mediation has emerged based on theoretical assumptions and Vygotsky through speeches and records of educators and students, divided into two subcategories: pedagogical mediations and the use of the calculator articulated to other mediators resources, which helped to unveil the initial research problem and objectives, directing the search for possible answers. The result of the analysis allowed us to assess that the objectives regarding the use of the calculator as an assistive technology resource, were included as contributed to the students could have more independence and autonomy in school activities involving mathematical concepts, offered new possibilities for learning and generated results for the students that went beyond the school walls.